PERAN ONLINE CELEBRITY ENDORSER PADA PEMBENTUKAN SELF-BRAND CONNECTION DAN NIAT BELI PRODUK FASHION LOKAL - Sheila Ramadani; Enny Haryanti (Ibs Press, 2023)
This study is modification of previous research (Ho et al.2020). Modifications are made by adding additional constructs, namely Self-Brand Connection and Brand Affection. This study uses 70 respondents who are follower are of Arief Muhammad and follower of one of the local brands, Prep studio. The research method used is a quantitative approach. The analysis in study uses PLS-SEM witch is supported by SmartPLS 3.0 software. The result of this study has implications for Arief Muhammad celebrity followers, to examine and analyze the role of online celebrity endorsers in the formation of Self-Brand connections and purchase intentions of local fashion product.